2015
DOI: 10.1103/physrevd.91.083013
|View full text |Cite
|
Sign up to set email alerts
|

Evidences of an innermost stable bound orbit predicted by general relativity from the amplitude of the twin-peak quasiperiodic oscillations

Abstract: The twin-peak high-frequency quasi-periodic oscillations (HF QPOs), observed in the power spectra of low-mass X-ray binaries, might carry relevant clues about the physics laws reigning close to a compact object. Their frequencies are typical of the orbital motion time-scales a few gravitational radii away from the compact object. The aim of the manuscript is to propose an intuitive model explaining that the energy carried by the lower HF QPO can be related to differences of potential energy released by clumps … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
(202 reference statements)
0
2
0
Order By: Relevance
“…A modeling of such trends is presented in Refs. [51,52] (hereafter GC15 and G17, respectively). Making use of the gravitational potential in the Schwarzschild metric we showed that the energy extracted by tides from clumps of plasma orbiting in the accretion disk might produce the rms amplitude of the HF QPOs seen in NS LMXBs.…”
Section: Introductionmentioning
confidence: 99%
“…A modeling of such trends is presented in Refs. [51,52] (hereafter GC15 and G17, respectively). Making use of the gravitational potential in the Schwarzschild metric we showed that the energy extracted by tides from clumps of plasma orbiting in the accretion disk might produce the rms amplitude of the HF QPOs seen in NS LMXBs.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work (Ref. [56], hereafter GC15) we have proposed that the amplitude and coherence of the lower HF QPO might originate from the energy released by a clump of plasma spiraling to inner orbits because of the work done by the tidal force, dissipating the orbital energy. In this paper we aim to investigate on the amplitude and coherence of the upper HF QPO [52].…”
Section: Introductionmentioning
confidence: 99%